Estruturas híbridas de nanotubos de carbono de parede simples e telúrio - Salomão, Francisco Carlos Carneiro Soares (2011)
In this work we use Raman spectroscopy and electron microscopy to characterize hybrid carbon nanotube single-wall and tellurium nanostructures. Carbon nanotubes are important nanostructures due to their electrical, optical and mechanical properties, which makes them attractive for many applications in nanotechnology. However, for a wide range of applications requires the functionalization of the nanotubes in order to better exploit their potential application. Within this area of hybrid structures formed with carbon nanotubes, we highlight the carbon nanotubes interacting with the family of the chalcogen elements, which make them suitable for applications ranging from photonics to biology. The hybrid SWCNT-Te samples were prepared through the generation of anionic species of CNTs, followed by capture of elemental tellurium, using single-wall carbon nanotubes prepared by different methods. Raman spectroscopy data show that the characteristics present in the samples of single wall carbon nanotubes and tellurium used in the functionalization and show differences in comparison with the characteristics observed in the hybrid samples. Changes in the G band frequency, asymmetry and width were observed after the functionalization. We noticed an increase in the relative intensity of band D in the sample in relation to the hybrid single-wall nanotubes used in the functionalization. In the observation of the modes between 100 and 1000 cm-1 we note the contribution of the RBM modes of single wall carbon nanotubes and the modes of tellurium. Raman modes associated with tellurium oxide were found in two of three hybrids samples, which are resonant modes for the laser line of 532 nm (2.33 eV). The process of removal of oxides, by dissolving in acetone PA in ultrasonic bath, proved to be efficient. Even after the removal of oxides, we can still observe the modes related to tellurium and carbon nanotubes in the Raman spectrum of hybrid sample. The electron microscope images show that the hybrid system is presented carbon nanotubes clusters with tellurium nanostructures.